Phlyctenular Conjunctivitis Treated with Homoeopathy: A Case Report - Sathye, Sandeep Sudhakar (Homœopathic Links, 2021)
Phlyctenular conjunctivitis (PC) is characterised by formation of a whitish nodule on bulbar conjunctiva near or at the limbus with a localised conjunctival congestion. It is considered as an allergic reaction to endogenous bacterial protein. Conventional treatment includes use of topical steroids in simple PC, but if there is some degree of secondary infection or corneal involvement then combined steroid-antibiotics are used though there are high chances of recurrence. Homoeopathic literature has medicines listed for PC. The case reported was a female aged 60 years suffering from PC in right eye since 5 days and had no relief from local conventional treatment. She had complaints of redness, foreign body sensation and whitish discharge from the eye. Phlycten was at 6 o'clock position below the limbus with much conjunctival congestion around it and in the lower fornix. Homoeopathic Hepar sulphuris 30C resolved nodule within a week but the patient had itching of eye at the inner canthus, especially in the morning. Homoeopathic Natrum muriaticum 30C helped to resolve conjunctival congestion in the fornix and itching of eye within a week. Both medicines were prescribed on the basis of local signs and symptoms. There was no recurrence in the last 5 months. This case report with ocular photographs during follow-up provides documentary evidence about effectiveness of homoeopathy in PC.
Keywords: homoeopathy; Hepar sulphuris; Natrum muriaticum; phlyctenular conjunctivitis